AN ALGARROBO, NATIVE TREE, AS A CULTURAL LANDSCAPE. CONFIGURATIONS ABOUT THE TOPIC "ALGARROBO- BUILDING SCHOLL" IN THE BARRIO MAPIC (RESISTENCIA, CHACO) - Rita Sandra Medina; Mónica Marisel Medina (Universidad Nacional del Nordeste, 2019)
The school of Educación Primaria N° 963 "Cacique Moreno" was founded in Mapic neighborhood in 1985 on request of the Qom community members. In that year, the community did not have a school building, the school had a precarious building. In the same year that precarious structure collpased after a strong storm; therefore, the principal (who was also a teacher) and the students decided to hang a blackboard in an algarrobo (a native tree). The algarrobo (mapic in Qom) was used as a classroom until 1988 approximately. Nowadays that algarrobo no longer exists; however, it is still present in the cultural memory of the qom community. In this paper we describe the semiospheres meanings (Lotman 1996) about the algarrobo and the space that the school building occupies now. For this, two complementary theoretical and methodological perspectives are adopted, semiotics and ethnography. These allow to recover the meanings stablished along the processes of school building creation and construction, and the meanings that are currently reconfigure about the algarrobo: 1) schoolalgarrobo in which there was no physical border to filter the cultural practices of the qom community and 2) school building that imposes a semi-sphere with fixed borders that obstruct the free flow of qom community habits since it establishes the idea of private property. The corpus is made up of regional and national newspapers from the '90s, school documents, semidirected interviews to members of the qom community and field notes collected during the years 2012-2015.